When fragments link: a bibliometric perspective on the development of fragment-based drug discovery. Issue 9 (September 2018) - Romasanta, Angelo K.S.; van der Sijde, Peter; Hellsten, Iina; Hubbard, Roderick E.; Keseru, Gyorgy M.; van Muijlwijk-Koezen, Jacqueline; de Esch, Iwan J.P.
Highlights: Through bibliometrics, we identify core papers and subdisciplines in FBDD research. FBDD's emergence was enabled by the transfer of knowledge from academia to industry. Network analysis shows that university-industry collaborations have grown over time. Abstract : Fragment-based drug discovery (FBDD) is a highly interdisciplinary field, rich in ideas integrated from pharmaceutical sciences, chemistry, biology, and physics, among others. To enrich our understanding of the development of the field, we used bibliometric techniques to analyze 3642 publications in FBDD, complementing accounts by key practitioners. Mapping its core papers, we found the transfer of knowledge from academia to industry. Co-authorship analysis showed that university–industry collaboration has grown over time. Moreover, we show how ideas from other scientific disciplines have been integrated into the FBDD paradigm. Keyword analysis showed that the field is organized into four interconnected practices: library design, fragment screening, computational methods, and optimization. This study highlights the importance of interactions among various individuals and institutions from diverse disciplines in newly emerging scientific fields. Teaser: We study the organizational aspects of the development of fragment-based drug discovery (FBDD), using tools from bibliometrics.